B mode ultrasonography and elastography in the evaluation of the pectineus muscle in dogs with hip dysplasia - Rossignoli, Pedro Paulo; Feliciano, Marcus Antônio Rossi [UNESP]; Minto, Bruno Watanabe [UNESP]; Maronezi, Marjury Cristina [UNESP]; Uscategui, Ricardo Andres Ramirez; Ido, Cléber Kazuo [UNESP]; Rolemberg, Daniele Santos [UNESP]; de Faria, Luís Guilherme [UNESP]; da Cruz, Igor Cezar Kniphoff [UNESP]; Aires, Luiz Paulo Nogueira [UNESP] (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2020)
The goal of this study was to describe and compare B mode and elastographic characteristics of the pectineus muscle of healthy dogs with dysplastic dogs. Thirty-one dogs (62 limbs) with hip dysplasia and 17 nondysplastic dogs (34 limbs) were evaluated. The hip dysplasia score was defined according to the Fédération Cynologique Internationale. Using B mode, echotexture and echogenicity of different regions of the pectineus muscle were evaluated. By means of ARFI elastography, qualitative (elastogram) and quantitative (shear wave velocity) tissue stiffness was assessed. B mode findings demonstrated a hyperechoic and heterogeneous pattern of the pectineus tissue in dogs with hip dysplasia, with compromised muscular delimitation and loss of its normal sonographic appearance, indicating the disease (P < 0.001). In the elastogram, it was observed that dogs with hip dysplasia showed less deformable pectineus muscle, with red colors (rigid). In quantitative evaluation, the different regions evaluated presented similar shear wave velocities; in dysplastic patients, shear wave velocities were higher compared to nondysplastic animals, with values higher than 2.85 m/s being strong indicators of the disease. Values of shear wave velocity were also influenced by the grade of dysplasia and age of the patients; however, there was no correlation with the depth of the evaluated area or body weight. It was concluded that pectineus muscle in dogs with hip dysplasia presents B mode and elastographic changes when compared to normal animals, demonstrating that these techniques might aid the evaluation of diseased dogs.
Keywords: Canine; Dysplasia; Elastography; Joint; Ultrasound